2022
DOI: 10.1088/1674-4926/43/11/112502
|View full text |Cite
|
Sign up to set email alerts
|

Colossal negative magnetoresistance from hopping in insulating ferromagnetic semiconductors

Abstract: Ferromagnetic semiconductor Ga1–x Mn x As1–y P y thin films go through a metal–insulator transition at low temperature where electrical conduction becomes driven by hopping of charge carriers. In this regime, we report a colossal negative magnetoresistance (CNMR) coexisting with a saturated magnetic moment, unlike in the traditional magnetic semiconductor Ga1– … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…2(a). No visible magnetic phase transition can be observed down to 2 K. Between 100 and 300 K, the susceptibility is nearly temperature-independent [32,33]. On the other hand, we found that the paramagnetic susceptibility in the temperature range of 300-400 K can be well fitted with the Curie-Weiss law as shown in fig.…”
Section: Resultsmentioning
confidence: 49%
“…2(a). No visible magnetic phase transition can be observed down to 2 K. Between 100 and 300 K, the susceptibility is nearly temperature-independent [32,33]. On the other hand, we found that the paramagnetic susceptibility in the temperature range of 300-400 K can be well fitted with the Curie-Weiss law as shown in fig.…”
Section: Resultsmentioning
confidence: 49%
“…Large AHE has also been found in SGlike Ge 1-x-y Sn x Mn y Te [30] . The AHE indicates strong spin-orbit coupling and spin polarization [31] . The hole concentrations of single crystal Na 1.09 (Zn 0.88 Mn 0.12 )Sb is 3.0 × 10 19 cm −3 at 100 K, which is over three times larger than that of parent phase.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is essential to study structural parameters and the possible phase transition under external pressures. Aforementioned (Ba,K)(Zn,Mn) 2 As 2 belongs to a new type of DMS with independent carrier and spin doping [24,25] , which is a key feature distinguished from (Ga,Mn)As [26] . Its parent material BaZn 2 As 2 has two phases.…”
Section: Introductionmentioning
confidence: 99%